Breath Biopsy Assessment of Liver Disease Using an Exogenous Volatile Organic Compound—Toward Improved Detection of Liver Impairment. Issue 9 (16th September 2020) - Ferrandino, Giuseppe; Orf, Isabel; Smith, Rob; Calcagno, Marzia; Thind, Anita Kaur; Debiram-Beecham, Irene; Williams, Megan; Gandelman, Olga; de Saedeleer, Alexandra; Kibble, Graham; Lydon, Anne Marie; Mayhew, Chris A.; et al.
Abstract : INTRODUCTION: Liver cirrhosis and its complication — hepatocellular carcinoma (HCC) — have been associated with increased exhaled limonene. It is currently unclear whether this increase is more strongly associated with the presence of HCC or with the severity of liver dysfunction. METHODS: We compared the exhaled breath of 40 controls, 32 cirrhotic patients, and 12 cirrhotic patients with HCC using the Breath Biopsy platform. Breath samples were analyzed by thermal desorption–gas chromatography–mass spectrometry. Limonene levels were compared between the groups and correlated to bilirubin, albumin, prothrombin time international normalized ratio, and alanine aminotransferase. RESULTS: Breath limonene concentration was significantly elevated in subjects with cirrhosis-induced HCC (M: 82.1 ng/L, interquartile range [IQR]: 16.33–199.32 ng/L) and cirrhosis (M: 32.6 ng/L, IQR: 6.55–123.07 ng/L) compared with controls (M: 6.2 ng/L, IQR: 2.62–9.57 ng/L) ( P value = 0.0005 and 0.0001, respectively) with no significant difference between 2 diseased groups ( P value = 0.37). Levels of exhaled limonene correlated with serum bilirubin ( R 2 = 0.25, P value = 0.0016, r = 0.51), albumin ( R 2 = 0.58, P value = 5.3e-8, r = −0.76), and international normalized ratio ( R 2 = 0.29, P value = 0.0003, r = 0.51), but not with alanine aminotransferase ( R 2 = 0.01, P value = 0.36, r = 0.19). DISCUSSION: Exhaled limonene levels are primarily affected by the presence of cirrhosis through reduced liver functional capacity, as indicated by limonene correlation with blood metrics of impaired hepatic clearance and protein synthesis capacity, without further alterations observed in subjects with HCC. This suggests that exhaled limonene is a potential non-invasive marker of liver metabolic capacity (see Visual abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A388 ).